Surgical informed consent practice and associated factors among adult postoperative patients in public hospitals of Mekelle, Tigray, Ethiopia 2023/2024. Cross sectional. - Fiseha Abadi Gebreanenia; Hailemarim Berhe Kahsay; Desta Siyoum Belay; Binyam Gebrehiwet Tesfay; Fissha Brhane Mesele; Mamush Gidey Abirha (PLoS ONE)
Background Substantial weaknesses and omissions of surgical informed consent are evident and the current elements of the surgical informed consent process are largely neglected in daily practice. This study aimed to assess surgical informed consent practice and associated factors among adult postoperative patients in public hospitals of Mekelle, Tigray, Ethiopia. Methods Institution based cross-sectional study was conducted among 314 adult postoperative patients in public hospitals of Mekelle, Tigray, Ethiopia. Participants were selected using systematic random sampling. A pretested interviewer-administered questionnaire was used to collect data. Descriptive, Descriptive, bivariate and multivariable logistic regression analyses were performed using statistical package for social science version 27. Result Only 35.8% (CI 95%, 30.6, 41) of the respondents were identified to have received the recommended (6 or more) components of surgical informed consent. Educational level [AOR 5.76 (1.02, 32.6)], timing of surgical informed consent delivery [AOR 3.27 (1.5, 7.11)], qualification of counselor who took surgical informed consent them [AOR3.185 (1.21, 8.38)], hospital type [AOR 2.85 (1.26, 6.46)], and duration of counseling [AOR 6.9 (3.33, 14.3)] were statistically significant at P<0.05. Conclusion Majority of participants did not receive comprehensive information during the surgical informed consent process in the study hospitals. To improve the delivery it is suggested that health professionals; create rapport with patient, spend more time during counseling.